Adaptive medial-axis approximation for sphere-tree construction - BRADSHAW, GARETH; O'SULLIVAN, CAROL ANN (My University, 2004)
Hierarchical object representations play an important role in performing efficient collision handling. Many different geometric primitives have been used to construct these representations, which allow areas of interaction to be localized quickly. For time-critical algorithms, there are distinct advantages to using hierarchies of spheres, known as sphere-trees, for object representation. This paper presents a novel algorithm for the construction of sphere-trees. The algorithm presented approximates objects, both convex and non-convex, with a higher degree of fit than existing algorithms. In the lower levels of the representations, there is almost an order of magnitude decrease in the number of spheres required to represent the objects to a given accuracy.
PUBLISHED
Keywords: Algorithms; Animation; Collision Handling